Green marketing as strategic comparative advantage of Serbian food companies on European Union market - Radnović, Branislav; Ilić, Milena; Živković, Zoran D. (REGIONAL AND BUSINESS STUDIES, 2011)
The Republic of Serbia is about to acquire candidate status to join the European Union. The strategic concept of the Republic of Serbia is to become a full member of the European Union as soon as possible. As a consequence of this, food companies from the Republic of Serbia intending to survive and succeed in the big market of the European Union (a market of several hundred million people) must be prepared on time for what European consumers demand. The European consumer is looking for, above all, a product that is reliable and safe in environmental terms. Every food company in Serbia that wants to satisfy European consumers must give green marketing practices an important place. To meet the stipulations of green marketing, a food product must be made from natural substances, have recyclable packaging, and move through an environmentally sustainable and safe system of distribution to its final consumers. The average European consumer knows what he wants in the ecological sense and requires that the food products he consumes meet those standards. He is looking for a „green” food product. Countries like the Republic of Serbia, with primary agricultural production, food, beverages and other production industries based on the use of natural and ecologically pure substances and materials are the countries that can gain a significant competitive advantage in this area of the European market. The goal of this paper is to show that green marketing can be a strategic comparative advantage for food companies from the Republic of Serbia entering the European Union's broader market.Keywords: green marketing, comparative advantage, food companies, Republic of Serbia, European Union